Low-cost regenerative sliding plate brick for converter slag stopping and preparation method of low-cost regenerative sliding plate brick

By adopting the combination of modified aluminum-zirconium carbon recycled material particles and co-milling powder, combined with phenolic resin and high-temperature nitriding sintering technology, the problems of rapid cast hole expansion, block drop and serious erosion during the steel discharge process of steel, the cast holes are rapidly expanded, block drop and erosion are severely improved, and the high-temperature performance and corrosion resistance of the sled bricks are achieved.

CN119874388APending Publication Date: 2025-04-25MAANSHAN LIER KAIYUAN NEW MATERIAL
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510043206.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the steel discharge process, existing converter slag barrier skateboard bricks are prone to rapid cast hole reaming, block drops, and serious erosion, resulting in safety hazards and short service life.

Method used

Using low-cost regeneration converter slag blocks, phenolic resin is added through the combination of modified aluminum-zirconium carbon recycled material particles and co-milling powder, and a non-oxide-enhanced phase is formed during high-temperature nitriding and firing, thereby improving the resistance to erosion and thermal shock resistance.

Benefits of technology

It significantly improves the high-temperature performance and corrosion resistance of skateboard bricks, extends service life, reduces production costs, and reduces the generation of easily hydrated AlN and Al4C3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a low-cost regenerative converter slag-stopping sliding plate brick and a preparation method thereof, and belongs to the technical field of refractory materials, the sliding plate brick comprises the following components by mass percentage: 59-62% of modified aluminum-zirconium-carbon regenerated material particles, 1-5% of silicon carbide particles, 35-40% of co-grinding powder, the total percentage being 100%, and 3.5-4.5% of additional phenolic resin. According to the low-cost regenerative sliding plate brick for converter slag stopping and the preparation method, the sliding plate brick is recycled after being used, aluminum-zirconium-carbon particles are obtained through the processes of sorting, iron removal, crushing, acid pickling, drying and the like, then the aluminum-zirconium-carbon particles are modified through metal aluminum to obtain modified aluminum-zirconium-carbon particles, and the modified aluminum-zirconium-carbon particles are of a matrix structure wrapping metal aluminum powder layer by layer; the prepared sliding plate brick is excellent in high-temperature performance and corrosion resistance, and the problems that in the prior art, a sliding plate brick for slag stopping is rapid in cast hole reaming, chipping and serious in corrosion are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a low-cost sliding plate brick for regeneration converter slag blocking and a preparation method thereof. Background Art

[0002] The converter sliding nozzle slag blocking technology has a 100% success rate of slag blocking, and has the advantages of improving alloy recovery rate, reducing impurities in steel, and improving steel grade cleanliness, and is widely used. The converter slag blocking slide consists of an upper slide, a lower slide, and an outer nozzle brick. The slide brick is the core functional element of the sliding nozzle to achieve slag blocking technology. Its service life and stability directly affect the use effect of the converter slide slag blocking technology.

[0003] The materials used for domestic converter slag-blocking slides are mostly aluminum-carbon, aluminum-zirconium-carbon and composite slides inlaid with zirconia materials. Although they can meet the requirements of on-site use, under the strong pressure and impact force during the steel tapping process, the upper slide plate will have too fast casting hole expansion, block falling and severe erosion, and the lower slide plate will have peeling and roughening in the anti-slip area, posing a major safety hazard to the entire converter slag-blocking system and is not conducive to the high life and fast-paced requirements in actual use. In addition, the inlaid zirconium slide plate has a high cost and a long construction period, and is easily affected by the poor thermal shock performance of the zirconia product itself and the unstable factors in the assembly process, resulting in a decrease in product quality stability. Summary of the invention

[0004] The purpose of the present invention is to provide a low-cost skateboard brick for regeneration converter slag blocking and a preparation method. The prepared skateboard brick has excellent high temperature performance and excellent corrosion resistance, and solves the problems of fast casting hole expansion, block falling and severe erosion of existing skateboard bricks for slag blocking mentioned in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a low-cost regeneration converter slag retaining slide brick, the slide brick composition is as follows by mass percentage: 59-62% of modified aluminum zirconium carbon regenerated material particles, 1%-5% of silicon carbide particles, 35%-40% of co-grinding powder, the total percentage is 100%, and 3.5%-4.5% of phenolic resin is added;

[0006] The co-grinding powder is prepared by uniformly mixing 17.8% to 22.8% of plate-shaped corundum fine powder, 5% to 10% of metal aluminum powder, 1% to 5% of α-Al2O3 micro powder, 1% to 5% of metal silicon powder, 1% to 3% of zirconium oxide powder, 0.4% to 1.2% of boron carbide and 0.2% to 0.6% of 95 micro silicon powder;

[0007] The modified aluminum-zirconium-carbon recycled material particles are prepared by recycling used skateboard bricks and modifying metal aluminum powder, comprising the following steps:

[0008] Step 1: Picking: Pick the waste skateboard bricks after the use of the converter skateboard slag retaining, the materials picked are mainly aluminum zirconium carbon;

[0009] Step 2: Deironing: Deironing the surface of the used aluminum zirconium carbon slide bricks after selection to remove surface impurities;

[0010] Step 3, crushing: crushing on a crusher, particles 3-1, 1-0;

[0011] Step 4: Decarburization: The crushed particles are decarburized in a shuttle kiln at 1000°C and kept at 1000°C for more than 4 hours;

[0012] Step 5, pickling: pickling the decarbonized particles with saturated hydrochloric acid and soaking them completely for more than 12 hours;

[0013] Step 6, drying: the aluminum zirconium carbon particles after acid washing are kept at a temperature between 250 and 300° C. for more than 12 hours to obtain aluminum zirconium carbon particles;

[0014] Step 7, mixing: add 50% of the aluminum zirconium carbon particles with a particle size of 3-1 and 40% of the aluminum zirconium carbon particles with a particle size of 1-0 into a mixer and grind for 5 minutes, add phenolic resin, grind for 3 to 5 minutes, add 10% of metal aluminum powder 325 mesh, grind for 12 to 18 minutes, and then discharge to obtain a slurry;

[0015] Step 8: Pressing: Press the above-mentioned clay into balls on a 1000-ton electric friction press; cool for 6 hours;

[0016] Step 9, drying: Place the above-mentioned spherical bricks in a drying kiln, set the initial temperature of the kiln to 50°C, and keep it at this temperature for 10 hours; raise the temperature to 80°C, and keep it at this temperature for 4 hours; raise the temperature to 120°C, and keep it at this temperature for 10 hours; raise the temperature to 150°C, and keep it at this temperature for 4 hours; raise the temperature to between 200 and 220°C, and keep it for 12 hours; the total drying time is more than 40 hours;

[0017] Step 10, crushing: Grind the spherical bricks in a crusher and a high-pressure ball grinder to obtain modified aluminum zirconium carbon particles 3-1 and 1-0.

[0018] Preferably, in step one of preparing the modified aluminum-zirconium-carbon recycled material particles, the Al2O3 content of the waste aluminum-zirconium-carbon skateboard bricks used is ≥75%, the ZrO2 content is ≥5%, the C content is ≥3%, and the SiO2 content is ≤15%.

[0019] Preferably, the particle size of the silicon carbide is 1-0 mm, the content of SiC in the silicon carbide is ≥97.5%, the content of Fe2O3 is ≤0.35%, the content of free carbon is ≤0.5%, the content of water is ≤0.2%, and the content of SiO2 is ≤0.5%;

[0020] The phenolic resin has a viscosity (25° C.) of 11000-17000 cP, a solid content (200° C.*2h) of ≥80%, and a residual carbon content (800° C.*7min) of ≥48%.

[0021] Preferably, the particle size of the α-Al2O3 micropowder is 5 um, the content of Al2O3 in the α-Al2O3 micropowder is ≥99.5%, the content of Fe2O3 is ≤0.08%, the content of SiO2 is ≤0.15%, and the content of R2O is ≤0.2%.

[0022] Preferably, the particle size of the metal aluminum powder is 325 meshes, the Al content in the metal aluminum powder is ≥99.5%, the active Al content is ≥99%, the Fe content is ≤0.2%, the Si content is ≤0.15%, and the Cu content is ≤0.1%.

[0023] Preferably, the particle size of the metallic silicon powder is 325 mm, the Si content in the metallic silicon powder is ≥98.2%, the Fe content is ≤0.8%, the Al content is ≤0.5%, and the Ca content is ≤0.9%.

[0024] Preferably, the particle size of the boron carbide is 325 mm, the content of B4C in the boron carbide is ≥ 95%, and the content of B 总 The content of ≥76.5%, C 总 The content of B2O3 is ≥20%, the content of B2O3 is ≤0.15%, and the content of C 游离 The content of Fe2O3 is ≤3%, the content of Al2O3 is ≤0.24%, the content of Al2O3 is ≤0.25%, and the content of SiO2 is ≤0.1%;

[0025] The particle size of the 95 micro silicon powder is 3-5um, the content of SiO2 in the 95 micro silicon powder is ≥95%, the content of Fe2O3 is ≤1%, the content of R2O is ≤1%, and the ignition loss is ≤1.5%.

[0026] Preferably, the D50 of the zirconium oxide powder is 2-3 um, the content of ZrO2+HfO2 in the zirconium oxide powder is ≥99%, the content of Fe2O3 is ≤0.1%, and the content of SiO2 is ≤0.3%.

[0027] Preferably, the particle size of the plate-like corundum fine powder is 200 meshes, the content of Al2O3 in the plate-like corundum fine powder is ≥99.5%, the content of Fe2O3 is ≤0.09%, and the content of R2O is ≤0.2%.

[0028] The present invention provides another technical solution: a method for preparing a low-cost sliding plate brick for regeneration converter slag blocking, comprising the following steps:

[0029] Step 1, particle batching: uniformly mixing modified aluminum zirconium carbon particles with a particle size of 3 to 1 mm, modified aluminum zirconium carbon particles with a particle size of 1 to 0 mm, and silicon carbide with a particle size of 1 to 0 mm according to weight percentage to obtain a particle batching;

[0030] Step 2, co-grinding powder preparation: plate-shaped corundum fine powder, α-Al2O3 powder, metal silicon powder, metal aluminum powder, boron carbide, 95 micro silicon powder and zirconium oxide powder are mixed uniformly according to weight percentage to prepare co-grinding powder;

[0031] Step 3, mixing: dry mix the granular aggregate with a wet mill for 3-5 minutes, then slowly add 3%-5% of the binder and wet mix for 5-8 minutes, then add the co-ground powder and mix for 25-30 minutes to obtain the mud;

[0032] Step 4: Forming: Press the above-mentioned mud material on a 1000t electric screw brick press to obtain a brick, and let it cool naturally for 12 hours;

[0033] Step 5, drying: Place the bricks in a drying kiln, set the initial temperature of the kiln to 50℃, and keep them at this temperature for 12 hours; raise the temperature to 80℃, and keep them at this temperature for 6 hours; raise the temperature to 120℃, and keep them at this temperature for 12 hours; raise the temperature to 150℃, and keep them at this temperature for 6 hours; raise the temperature to between 200 and 250℃, and keep them at this temperature for 12 hours; the total drying time is more than 48 hours; select qualified semi-finished products after leaving the kiln;

[0034] Step 6, nitriding firing: nitriding firing is carried out in a 15m shuttle kiln, the temperature in the kiln is raised by 20-25℃ / h, and the temperature is kept at 1650-1680℃ for 16h, the firing time is 81-99h, the cooling time is 50-65h, and the kiln door is opened only after cooling to below 80℃; nitrogen is introduced into the shuttle kiln during the firing process;

[0035] Step 7: Hoop: The iron hoop is located in the middle, the weld of the iron hoop shall not exceed 1mm, and the gap between the iron hoop and the slide plate shall not exceed 1mm;

[0036] Step 8, grinding: grinding on a CNC vertical axis rotary table surface grinder, the flatness of the working surface of the slide plate is less than 0.05mm, and drying is carried out using an infrared dryer after grinding;

[0037] Step nine: Finally, veneer, coating, inspection and packaging are performed to obtain the finished product.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The present invention proposes a low-cost skateboard brick for regenerating converter slag retaining and a preparation method. The skateboard bricks are recycled after use, and aluminum zirconium carbon particles are obtained through sorting, iron removal, crushing, pickling, drying and other processes. The aluminum zirconium carbon particles are then modified by metallic aluminum to obtain modified aluminum zirconium carbon particles. The modified aluminum zirconium carbon particles have a matrix structure with layers of metallic aluminum powder wrapped in them.

[0040] 2. The present invention proposes a low-cost slide brick for regeneration converter slag blocking and a preparation method. By adding excessive plastic metal aluminum, the metal aluminum, the carbon source dispersed after carbonization of phenolic resin and the N2 in the atmosphere generate in situ non-oxide reinforcement phase Al2OC-AlNss during high-temperature nitriding and sintering. The layered matrix structure of the modified aluminum-zirconium-carbon particles increases the activity of the reaction, and an interlaced crystal phase distribution can be formed in the matrix, thereby improving the corrosion resistance and thermal shock resistance of the slide brick, and reducing the generation of easily hydrated AlN and Al4C3, solving the problem of easy hydration of the slide brick.

[0041] 3. The present invention proposes a low-cost skateboard brick for regeneration converter slag blocking and a preparation method. By adding metallic silicon powder, metallic silicon, metallic aluminum powder, zirconium oxide powder and the lack of O2 in the pores undergo complex chemical reactions during the high-temperature nitriding and firing process, and the high-temperature reinforcing phase high-zirconium mullite phase is produced in situ, thereby improving the high-temperature strength of the skateboard brick. At the same time, the layered matrix structure of the modified aluminum-zirconium-carbon particles increases the activity of the reaction, and an interlaced crystal phase distribution can be formed in the matrix.

[0042] 4. The present invention proposes a low-cost regenerative converter slag-blocking slide brick and a preparation method. No carbon source is added, and the carbon in the binder phenolic resin is completely converted into non-oxide reinforcing phases SiC and Al2OC-AlNss during the nitriding and firing process, which can meet the smelting needs of clean steel. Compared with ordinary aluminum-zirconium-carbon slide bricks, the low-cost regenerative converter slag-blocking slide brick of the present invention has a slide improvement from 15 times to more than 18 times. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] This embodiment provides the following technical solutions:

[0046] A low-cost regeneration converter slag retaining slide brick, the slide brick composition is as follows by mass percentage: 30% of modified aluminum zirconium carbon particles 3-1, 30% of modified aluminum zirconium carbon particles 1-0, 5% of silicon carbide particles, 35% of co-ground powder, the total percentage is 100%, and 3.5% of a binder phenolic resin is added;

[0047] The co-grinding powder is prepared by uniformly mixing 20.4% of plate-shaped corundum fine powder, 5% of metal aluminum powder, 5% of α-Al2O3 micro powder, 1% of metal silicon powder, 3% of zirconium oxide powder, 0.4% of boron carbide and 0.2% of 95 micro silicon powder;

[0048] In addition, the modified aluminum zirconium carbon recycled material particles are prepared by recycling the used skateboard bricks and modifying the metal aluminum powder, including the following steps:

[0049] Step 1: Picking: Pick the waste skateboard bricks after the use of the converter skateboard slag retaining, the materials picked are mainly aluminum zirconium carbon;

[0050] Step 2: Deironing: Deironing the surface of the used aluminum zirconium carbon slide bricks after selection to remove surface impurities;

[0051] Step 3, crushing: crushing on a crusher, particles 3-1, 1-0;

[0052] Step 4: Decarburization: The crushed particles are decarburized in a shuttle kiln at 1000°C and kept at 1000°C for more than 4 hours;

[0053] Step 5, pickling: pickling the decarbonized particles with saturated hydrochloric acid and soaking them completely for more than 12 hours;

[0054] Step 6, drying: the aluminum zirconium carbon particles after acid washing are kept at a temperature between 250 and 300° C. for more than 12 hours to obtain aluminum zirconium carbon particles;

[0055] Step 7, mixing: add 50% of the aluminum zirconium carbon particles with a particle size of 3-1 and 40% of the aluminum zirconium carbon particles with a particle size of 1-0 into a mixer and grind for 5 minutes, add phenolic resin, grind for 3 to 5 minutes, add 10% of metal aluminum powder 325 mesh, grind for 12 to 18 minutes, and then discharge to obtain a slurry;

[0056] Step 8: Pressing: Press the above-mentioned clay into balls on a 1000-ton electric friction press; cool for 6 hours;

[0057] Step 9, drying: Place the above-mentioned spherical bricks in a drying kiln, set the initial temperature of the kiln to 50°C, and keep it at this temperature for 10 hours; raise the temperature to 80°C, and keep it at this temperature for 4 hours; raise the temperature to 120°C, and keep it at this temperature for 10 hours; raise the temperature to 150°C, and keep it at this temperature for 4 hours; raise the temperature to between 200 and 220°C, and keep it for 12 hours; the total drying time is more than 40 hours;

[0058] Step 10, crushing: Grind the spherical bricks in a crusher and a high-pressure ball grinder to obtain modified aluminum zirconium carbon particles 3-1 and 1-0.

[0059] Specifically, in step one of preparing modified aluminum-zirconium-carbon recycled material particles, the waste aluminum-zirconium-carbon skateboard bricks used have an Al2O3 content of ≥75%, a ZrO2 content of ≥5%, a C content of ≥3%, and a SiO2 content of ≤15%.

[0060] Specifically, the particle size of silicon carbide is 1-0 mm, the content of SiC in silicon carbide is ≥97.5%, the content of Fe2O3 is ≤0.35%, the content of free carbon is ≤0.5%, the content of water is ≤0.2%, and the content of SiO2 is ≤0.5%;

[0061] The viscosity of the phenolic resin (25°C) is 11000-17000 cP, the solid content (200°C*2h) is ≥80%, and the residual carbon content (800°C*7min) is ≥48%.

[0062] Specifically, the particle size of the α-Al2O3 micropowder is 5 um, the content of Al2O3 in the α-Al2O3 micropowder is ≥99.5%, the content of Fe2O3 is ≤0.08%, the content of SiO2 is ≤0.15%, and the content of R2O is ≤0.2%.

[0063] Specifically, the particle size of the metal aluminum powder is 325 meshes, the Al content in the metal aluminum powder is ≥99.5%, the active Al content is ≥99%, the Fe content is ≤0.2%, the Si content is ≤0.15%, and the Cu content is ≤0.1%.

[0064] Specifically, the particle size of the metal silicon powder is 325 mm, the Si content in the metal silicon powder is ≥98.2%, the Fe content is ≤0.8%, the Al content is ≤0.5%, and the Ca content is ≤0.9%.

[0065] Specifically, the particle size of boron carbide is 325 mm, the content of B4C in boron carbide is ≥ 95%, and the content of B 总 The content of ≥76.5%, C 总 The content of B2O3 is ≥20%, the content of B2O3 is ≤0.15%, and the content of C 游离The content of Fe2O3 is ≤3%, the content of Al2O3 is ≤0.24%, the content of Al2O3 is ≤0.25%, and the content of SiO2 is ≤0.1%;

[0066] The particle size of 95 microsilica powder is 3-5um. The content of SiO2 in 95 microsilica powder is ≥95%, the content of Fe2O3 is ≤1%, the content of R2O is ≤1%, and the loss on ignition is ≤1.5%.

[0067] Specifically, the D50 of the zirconium oxide powder is 2-3 um, the content of ZrO2+HfO2 in the zirconium oxide powder is ≥99%, the content of Fe2O3 is ≤0.1%, and the content of SiO2 is ≤0.3%.

[0068] Specifically, the particle size of the plate-like corundum fine powder is 200 meshes, the content of Al2O3 in the plate-like corundum fine powder is ≥99.5%, the content of Fe2O3 is ≤0.09%, and the content of R2O is ≤0.2%.

[0069] In order to better demonstrate the process of realizing a low-cost regenerative converter slag retaining slide brick, this embodiment proposes a method for preparing a low-cost regenerative converter slag retaining slide brick, comprising the following steps:

[0070] Step 1, particle batching: uniformly mixing modified aluminum zirconium carbon particles with a particle size of 3 to 1 mm, modified aluminum zirconium carbon particles with a particle size of 1 to 0 mm, and silicon carbide with a particle size of 1 to 0 mm according to weight percentage to obtain a particle batching;

[0071] Step 2, co-grinding powder preparation: plate-shaped corundum fine powder, α-Al2O3 powder, metal silicon powder, metal aluminum powder, boron carbide, 95 micro silicon powder and zirconium oxide powder are mixed uniformly according to weight percentage to prepare co-grinding powder;

[0072] Step 3, mixing: dry mix the granular aggregate with a wet mill for 3-5 minutes, then slowly add 3%-5% of the binder and wet mix for 5-8 minutes, then add the co-ground powder and mix for 25-30 minutes to obtain the mud;

[0073] Step 4: Forming: Press the above-mentioned mud material on a 1000t electric screw brick press to obtain a brick, and let it cool naturally for 12 hours;

[0074] Step 5, drying: place the bricks in a drying kiln, set the initial temperature of the kiln to 50℃, and keep it at this temperature for 12 hours; raise the temperature to 80℃, and keep it at this temperature for 6 hours; raise the temperature to 120℃, and keep it at this temperature for 12 hours; raise the temperature to 150℃, and keep it at this temperature for 6 hours; raise the temperature to 250℃, and keep it at this temperature for 12 hours; the total drying time is 50 hours; select qualified semi-finished products after leaving the kiln;

[0075] Step 6, nitriding firing: nitriding firing is carried out in a 15m shuttle kiln, the temperature in the kiln is raised by 20℃ / h, kept at 1650℃ for 16h, the firing time is 98h, the cooling time is 50h, and the kiln door is opened only after cooling to below 80℃; nitrogen is introduced into the shuttle kiln during the firing process;

[0076] Step 7: Hoop: The iron hoop is located in the middle, the weld of the iron hoop shall not exceed 1mm, and the gap between the iron hoop and the slide plate shall not exceed 1mm;

[0077] Step 8, grinding: grinding on a CNC vertical axis rotary table surface grinder, the flatness of the working surface of the slide plate is less than 0.05mm, and drying is carried out using an infrared dryer after grinding;

[0078] Step nine: Finally, veneer, coating, inspection and packaging are performed to obtain the finished product.

[0079] Example 2

[0080] The low-cost regenerative converter slag retaining slide bricks of this embodiment have the same composition and weight percentage as shown in Table 1, and the preparation method is the same as that of Example 1.

[0081] Example 3

[0082] The low-cost regenerative converter slag retaining slide bricks of this embodiment have the same composition and weight percentage as shown in Table 1, and the preparation method is the same as that of Example 1.

[0083] Table 1 Granularity and percentage of ingredients used in various embodiments of the present invention

[0084]

[0085] The physical and chemical properties and average service life parameters of the low-cost regeneration converter slag retaining slide brick of the present invention and the ordinary aluminum zirconium carbon slide brick are compared in Table 2:

[0086] Table 2 Comparison of the physical and chemical properties and average service life of the low-cost regeneration converter slag retaining slide brick of the present invention and the ordinary aluminum zirconium carbon slide brick

[0087]

[0088] The low-cost regenerative converter slag-blocking skateboard bricks obtained in the above embodiment were tried out on a certain company's converter, and after the test, the skateboard bricks of the present invention were compared with ordinary aluminum zirconium carbon products for erosion, cracks, etc. The service life of the skateboard of the present invention reaches more than 18 times, with an average diameter expansion of 40mm (original aperture 140mm), and an average erosion rate of 2.22mm / time. By comparing the measured data with ordinary aluminum zirconium carbon skateboard bricks, the average erosion rate of the skateboard of the present invention is 2.22mm / time, which is better than the average erosion rate of 3.33mm / furnace of existing aluminum zirconium carbon skateboard bricks. Wear resistance of the skateboard: the skateboard bricks have many cracks on the surface, loose structure, and poor thermal shock resistance; the skateboard of the present invention has a good surface condition after use, and has good bonding strength and thermal shock resistance.

[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A low-cost regeneration converter slag retaining slide brick, characterized in that: The skateboard brick composition is as follows by mass percentage: 59% to 62% of modified aluminum zirconium carbon recycled material particles, 1% to 5% of silicon carbide particles, 35% to 40% of co-ground powder, the total percentage is 100%, and 3.5% to 4.5% of phenolic resin is added; The co-grinding powder is prepared by uniformly mixing 17.8% to 22.8% of plate-shaped corundum fine powder, 5% to 10% of metal aluminum powder, 1% to 5% of α-Al2O3 micro powder, 1% to 5% of metal silicon powder, 1% to 3% of zirconium oxide powder, 0.4% to 1.2% of boron carbide and 0.2% to 0.6% of 95 micro silicon powder; The modified aluminum-zirconium-carbon recycled material particles are prepared by recycling used skateboard bricks and modifying metal aluminum powder, comprising the following steps: Step 1: Picking: Pick the waste skateboard bricks after the use of the converter skateboard slag retaining, the materials picked are mainly aluminum zirconium carbon; Step 2: Deironing: Deironing the surface of the used aluminum zirconium carbon slide bricks after selection to remove surface impurities; Step 3, crushing: crushing on a crusher, particles 3-1, 1-0; Step 4: Decarburization: The crushed particles are decarburized in a shuttle kiln at 1000°C and kept at 1000°C for more than 4 hours; Step 5, pickling: pickling the decarbonized particles with saturated hydrochloric acid and soaking them completely for more than 12 hours; Step 6, drying: the aluminum zirconium carbon particles after acid washing are kept at a temperature between 250 and 300° C. for more than 12 hours to obtain aluminum zirconium carbon particles; Step 7, mixing: add 50% of the aluminum zirconium carbon particles with a particle size of 3-1 and 40% of the aluminum zirconium carbon particles with a particle size of 1-0 into a mixer and grind for 5 minutes, add phenolic resin, grind for 3 to 5 minutes, add 10% of metal aluminum powder 325 mesh, grind for 12 to 18 minutes, and then discharge to obtain a slurry; Step 8: Pressing: Press the above-mentioned clay into balls on a 1000-ton electric friction press; cool for 6 hours; Step 9, drying: Place the above-mentioned spherical bricks in a drying kiln, set the initial temperature of the kiln to 50°C, and keep it at this temperature for 10 hours; raise the temperature to 80°C, and keep it at this temperature for 4 hours; raise the temperature to 120°C, and keep it at this temperature for 10 hours; raise the temperature to 150°C, and keep it at this temperature for 4 hours; raise the temperature to between 200 and 220°C, and keep it for 12 hours; the total drying time is more than 40 hours; Step 10, crushing: Grind the spherical bricks in a crusher and a high-pressure ball grinder to obtain modified aluminum zirconium carbon particles 3-1 and 1-0.

2. The low-cost regeneration converter slag retaining slide brick according to claim 1, characterized in that: In step 1 of preparing the modified aluminum-zirconium-carbon recycled material particles, the waste aluminum-zirconium-carbon skateboard bricks used have an Al2O3 content of ≥75%, a ZrO2 content of ≥5%, a C content of ≥3%, and a SiO2 content of ≤15%.

3. The low-cost regeneration converter slag retaining slide brick according to claim 2 is characterized in that: The particle size of the silicon carbide is 1-0 mm, the content of SiC in the silicon carbide is ≥97.5%, the content of Fe2O3 is ≤0.35%, the content of free carbon is ≤0.5%, the content of water is ≤0.2%, and the content of SiO2 is ≤0.5%; The phenolic resin has a viscosity (25° C.) of 11000-17000 cP, a solid content (200° C.*2h) of ≥80%, and a residual carbon content (800° C.*7min) of ≥48%.

4. The low-cost regeneration converter slag retaining slide brick according to claim 3 is characterized by: The particle size of the α-Al2O3 micropowder is 5um, the content of Al2O3 in the α-Al2O3 micropowder is ≥99.5%, the content of Fe2O3 is ≤0.08%, the content of SiO2 is ≤0.15%, and the content of R2O is ≤0.2%.

5. The low-cost regeneration converter slag retaining slide brick according to claim 4, characterized in that: The particle size of the metal aluminum powder is 325 meshes, the Al content in the metal aluminum powder is ≥99.5%, the active Al content is ≥99%, the Fe content is ≤0.2%, the Si content is ≤0.15%, and the Cu content is ≤0.1%.

6. The low-cost regeneration converter slag retaining slide brick according to claim 5, characterized in that: The particle size of the metal silicon powder is 325 mm, the Si content in the metal silicon powder is ≥98.2%, the Fe content is ≤0.8%, the Al content is ≤0.5%, and the Ca content is ≤0.9%.

7. The low-cost regeneration converter slag retaining slide brick according to claim 6, characterized in that: The particle size of the boron carbide is 325 mm, the content of B4C in the boron carbide is ≥ 95%, and the content of B 总 The content of ≥76.5%, C 总 The content of B2O3 is ≥20%, the content of B2O3 is ≤0.15%, and the content of C 游离 The content of Fe2O3 is ≤3%, the content of Al2O3 is ≤0.24%, the content of Al2O3 is ≤0.25%, and the content of SiO2 is ≤0.1%; The particle size of the 95 micro silicon powder is 3-5um, the content of SiO2 in the 95 micro silicon powder is ≥95%, the content of Fe2O3 is ≤1%, the content of R2O is ≤1%, and the ignition loss is ≤1.5%.

8. The low-cost regeneration converter slag retaining slide brick according to claim 7, characterized in that: The D50 of the zirconium oxide powder is 2-3 um, the content of ZrO2+HfO2 in the zirconium oxide powder is ≥99%, the content of Fe2O3 is ≤0.1%, and the content of SiO2 is ≤0.3%.

9. The low-cost regeneration converter slag retaining slide brick according to claim 8, characterized in that: The particle size of the plate-like corundum fine powder is 200 meshes, the content of Al2O3 in the plate-like corundum fine powder is ≥99.5%, the content of Fe2O3 is ≤0.09%, and the content of R2O is ≤0.2%.

10. The method for preparing a low-cost sliding plate brick for regeneration converter slag blocking according to claim 9, characterized in that: The steps include: Step 1, particle batching: uniformly mixing modified aluminum zirconium carbon particles with a particle size of 3 to 1 mm, modified aluminum zirconium carbon particles with a particle size of 1 to 0 mm, and silicon carbide with a particle size of 1 to 0 mm according to weight percentage to obtain a particle batching; Step 2, co-grinding powder preparation: plate-shaped corundum fine powder, α-Al2O3 powder, metal silicon powder, metal aluminum powder, boron carbide, 95 micro silicon powder and zirconium oxide powder are mixed uniformly according to weight percentage to prepare co-grinding powder; Step 3, mixing: dry mix the granular aggregate with a wet mill for 3-5 minutes, then slowly add 3%-5% of the binder and wet mix for 5-8 minutes, then add the co-ground powder and mix for 25-30 minutes to obtain the mud; Step 4: Forming: Press the above-mentioned mud material on a 1000t electric screw brick press to obtain a brick, and let it cool naturally for 12 hours; Step 5, drying: Place the bricks in a drying kiln, set the initial temperature of the kiln to 50℃, and keep them at this temperature for 12 hours; raise the temperature to 80℃, and keep them at this temperature for 6 hours; raise the temperature to 120℃, and keep them at this temperature for 12 hours; raise the temperature to 150℃, and keep them at this temperature for 6 hours; raise the temperature to between 200 and 250℃, and keep them at this temperature for 12 hours; the total drying time is more than 48 hours; select qualified semi-finished products after leaving the kiln; Step 6, nitriding firing: nitriding firing is carried out in a 15m shuttle kiln, the temperature in the kiln is raised by 20-25℃ / h, and the temperature is kept at 1650-1680℃ for 16h, the firing time is 81-99h, the cooling time is 50-65h, and the kiln door is opened only after cooling to below 80℃; nitrogen is introduced into the shuttle kiln during the firing process; Step 7: Hoop: The iron hoop is located in the middle, the weld of the iron hoop shall not exceed 1mm, and the gap between the iron hoop and the slide plate shall not exceed 1mm; Step 8, grinding: grinding on a CNC vertical axis rotary table surface grinder, the flatness of the working surface of the slide plate is less than 0.05mm, and drying is carried out using an infrared dryer after grinding; Step nine: Finally, veneer, coating, inspection and packaging are performed to obtain the finished product.

Citation Information

Cited By

  • Preparation method of converter slag-stopping sliding plate brick and product

    CN120757392A

  • Renewable sliding plate brick as well as preparation method and application thereof

    CN122344110A